Revealing the metabolic potential and environmental adaptation of nematophagous fungus, Purpureocillium lilacinum, derived from hadal sediment - Li, Yongqi; Zhang, Changhao; Zhong, Maosheng; Hu, Shenao; Cui, Yukun; Fang, Jiasong; Yu, Xi (Frontiers in Microbiology, 2024)
The extreme environment shapes fungi in deep-sea sediments with novel metabolic capabilities. The ubiquity of fungi in deep-sea habitats supports their significant roles in these ecosystems. However, there is limited research on the metabolic activities and adaptive mechanisms of filamentous fungi in deep-sea ecosystems. In this study, we investigated the biological activities, including antibacterial, antitumor and nematicidal activity of Purpureocillium lilacinum FDZ8Y1, isolated from sediments of the Mariana Trench. A key feature of P. lilacinum FDZ8Y1 was its tolerance to high hydrostatic pressure (HHP), up to 110 MPa. We showed that HHP affected its vegetative growth, development, and production of secondary metabolites, indicating the potential for discovering novel natural products from hadal fungi. Whole-genome sequencing of P. lilacinum FDZ8Y1 revealed the metabolic potential of this piezotolerant fungus in carbon (carbohydrate metabolism), nitrogen (assimilatory nitrate reduction and protein degradation) and sulfur cycling processes (assimilatory sulfate reduction).Transcriptomic analysis under elevated HHP showed that P. lilacinum FDZ8Y1 may activate several metabolic pathways and stress proteins to cope with HHP, including fatty acid metabolism, the antioxidant defense system, the biosynthetic pathway for secondary metabolites, extracellular enzymes and membrane transporters. This study provides valuable insights into the metabolic potential and adaptation mechanisms of hadal fungi to the challenging conditions of the hadal environment.